Valproate-Induced Model of Autism in Adult Zebrafish: A Systematic Review - Diletta Camussi; Maria Marchese; Ferdinando Nicoletti; Filippo Maria Santorelli; Asahi Ogi (Cells)
Autism spectrum disorder (ASD) is a neurodevelopmental disorder characterized by deficits in social skills and the presence of repetitive and restricted behaviors and interests. The social behavior of the zebrafish (Danio rerio) makes this organism a valuable tool for modeling ASD in order to explore the social impairment typical of this disorder. In addition to transgenic models, exposure of zebrafish embryos to valproic acid (VPA) has been found to produce ASD-like symptoms. This review first sets out to examine the existing literature on adult social behavior in the zebrafish VPA-induced model of autism, and the authors also aim to identify the ideal VPA dosage able to induce a persistent and long-lasting ASD-like phenotype while minimizing the suffering and distress of research animals in compliance with the principles of replacement, refinement, and reduction (3Rs).